Fourfold subalterns: Catalan, women, translators, and theorists. Issue 3 (1st September 2016) - Bacardí, Montserrat; Godayol, Pilar
Abstract: In Europe's cultural poly-system, the two women translators examined in this paper can be considered subalterns four times over: because of their nation (Catalonia), gender (female), intellectual activity (translation), and genre (for daring to write translation theory). Born in the late nineteenth century, Carme Montoriol (Barcelona, 1893–1966) and Maria Antònia Salvà (Palma, Majorca, 1869 – Llucmajor, Majorca, 1958) were pioneering women of letters. These two, of different origins, were among the first Catalan women translators to reflect on translation in the male-dominated literary circles of the early twentieth century. In 1928, Montoriol added "Brief Introductory Notes" to her Catalan translation of all of Shakespeare's sonnets ( Els sonets de Shakespeare ). In 1945, at the height of the terrible repression of Catalan language and literature by Franco's dictatorship (1936–1975), Salvà wrote a brief but pertinent "Introduction" to her translation of the poems of St Thérèse of Lisieux ( Poemes de santa Teresa de l'Infant Jesús ). By framing these two paradigmatic translations and accompanying forewords in their context, we will attempt to ascertain how and why these Catalan translators (despite the restrictive, hostile political environment in the case of Salvà) quietly entered the realm of authorship, explained their work, and placed it in the limelight, how and why they employed what appeared to be a "discreet", "humble" tone and discourse, and an almost colloquial rhetoric, and what relatively original translation ideas they held.